Cell lines in Diabetes Research: A Review - Patel, M.B.; Mishra, S.H. (Pharmacognosy Reviews)
Animal models have been used extensively in diabetes research. Early studies used pancreatectomised dogs to confirm the central role of the pancreas in glucose homeostasis, culminating in the discovery and purification of insulin. Selective inbreeding has produced several strains of animal that are considered reasonable models of Type I diabetes, Type II diabetes and related phenotypes such as obesity and insulin resistance. Today, animal experimentation is contentious and subject to legal and ethical restrictions that vary throughout the world. This review gives an overview on the various cell lines used to evaluate the new chemical entities (NCEs) for their hypoglycemic effects. These cell lines are described with their origin/source, characteristic features, mechanism(s), advantages/disadvantages and applications in diabetes research in screening of NCEs for type I and type II diabetes. In addition, it especially describes the appropriate selection and usefulness of different cell line in preclinical testing of various NCEs for the treatment of diabetes.
Keywords: Cell lines; diabetes research; type I diabetes; type II diabetes